Reading the Twelve as One: Hosea 13 as an Introduction to Book of the Twelve (The Minor Prophets) - Bowman, Craig (Stone-Campbell journal, 2006)
The opening chapters of Hosea, positionally and rhetorically, set a toneand a rhythm for the whole Book of the Twelve, especially if the finaleditor of the BT strategically ordered the prophetic books that followHosea around a few key terms that are based in Hosea 13. Thus, areading strategy emerges, which when discerned clarifies the rhetoricalfunction of the Hosea prologue as a guide for reading the book of theMinor Prophets together as one. Incorporating recent work by OdilSteck, emphasizing the intrinsic "reading directions and readingpaths" supplied by the BT itself, and by William Schniedewind regardingthe most plausible periods for the formation of biblical textuality,literacy, and preservation, this paper argues for a simpler model ofcomposition, redaction, and editing for the BT compliant with internalrhetorical clues within the BT itself and with external evidence forthe development of writing and reading within the social history ofancient Israel.